Correction: Gyroid structured aqua-sheets with sub-nanometer thickness enabling 3D fast proton relay conduction. Issue 35 (4th September 2020) - Kobayashi, Tsubasa; Li, Ya-xin; Ono, Ayaka; Zeng, Xiang-bing; Ichikawa, Takahiro
Abstract : Correction for 'Gyroid structured aqua-sheets with sub-nanometer thickness enabling 3D fast proton relay conduction' by Tsubasa Kobayashi et al., Chem. Sci., 2019, 10, 6245–6253, DOI: ; 10.1039/C9SC00131J .